A METHOD OF CALCULATING FILTRATION RATE OF AN INFILTRATION WATER INTAKE IN KURSK REGION - Bredihin, Vladimir Viktorovich; Akulshin, Alexander Anatolyevich; Bredihina, Natalia Vladimirovna; Pereverzeva, Valeria Sergeevna (Journal of Applied Engineering Science, 2017)
The paper describes a method to calculate filtration rates that can be used to find equipment with best performance considering the well specific features. The method is presented by using an example of an infiltration intake in Kursk (Black Soil Region, Russia). The paper contains the formula to calculate filtration rates of various grounds for different well types located in different hydrological and hydrogeological areas.   The applied equations are built on Dupuit equations.
Keywords: Waterbearing bed; Filtration rate; Well; Ground waters; Dupuit equation